Use of U-isotopes in exploring groundwater flow and inter-aquifer leakage in the south-western margin of the Great Artesian Basin and Arckaringa Basin, central Australia. (November 2018) - Priestley, Stacey C.; Payne, Timothy E.; Harrison, Jennifer J.; Post, Vincent E.A.; Shand, Paul; Love, Andrew J.; Wohling, Daniel L.
Abstract: The distribution of uranium isotopes ( 238 U and 234 U) in groundwaters of the south-western margin of the Great Artesian Basin (GAB), Australia, and underlying Arckaringa Basin were examined using groundwater samples and a sequential extraction of aquifer sediments. Rock weathering, the geochemical environment and α-recoil of daughter products control the 238 U and 234 U isotope distributions giving rise to large spatial variations. Generally, the shallowest aquifer (J aquifer) contains groundwater with higher 238 U activity concentrations and 234 U/ 238 U activity ratios close to secular equilibrium. However, the source input of uranium is spatially variable as intermittent recharge from ephemeral rivers passes through rocks that have already undergone extensive weathering and contain low 238 U activity concentrations. Other locations in the J aquifer that receive little or no recharge contain higher 238 U activity concentrations because uranium from localised uranium-rich rocks have been leached into solution and the geochemical environment allows the uranium to be kept in solution. The geochemical conditions of the deeper aquifers generally result in lower 238 U activity concentrations in the groundwater accompanied by higher 234 U/ 238 U activity ratios. The sequential extraction of aquifer sediments showed that α-recoil of 234 U from the solid mineral phases into the groundwater, rather than dissolution of, or exchange with the groundwater accessible minerals in the aquifer, caused enrichment of groundwater 234 U/ 238 U activity ratios in the Boorthanna Formation. Decay of 238 U in uranium-rich coatings on J aquifer sediments caused resistant phase 234 U/ 238 U activity ratio enrichment. The groundwater 234 U/ 238 U activity ratio is dependent on groundwater residence time or flow rate, depending on the flow path trajectory. Thus, uranium isotope variations confirmed earlier groundwater flow interpretations based on other tracers; however, spatial heterogeneity, and the lack of clear regional correlations, made it difficult to identify recharge and inter-aquifer leakage. Highlights: Geochemistry, weathering, and α-recoil control uranium isotope distributions. Uranium isotope distributions were used to identify groundwater flow processes. Sequential extractions confirm α-recoil causes disequilibrium of uranium isotopes.